Strategi Pemasaran Gula Semut Aren Guseta (Kelompok Tani Mutiara Kecamatan Lareh Sago Halaban Kabupaten Limapuluh Kota) - Calista, Mila Quinsy (LPPM Universitas Malikussaleh - Indonesia, 2022)
Mutiara Farmers Group exist since 2015 and become the first farmers group in Limapuluh Kota regency produced palm sugar. This product had brand called by Guseta. Becoming the first palm sugar product, it was not made this product known by public. This product need some analysis to used for make some marketing strategic. The tools are IFAS matrix, EFAS matrix, IE matrix, SWOT matrix, and QSPM matrix for make the best recommendation of marketing strategy for Guseta. The result of using the tools are had the total score of the internal key factor are 2.96, with the biggest strength are the product have PIRT and this product is chemical free and also sor the biggest weakness is less of distribution. For score total of the eksternal key factor are 3.18, with the biggest opportunity is technology and information development, and for the biggest threat is depends on weather. In IE matrix show that the marketing of Guseta in cell II which is in grow built. The result of SWOT analysis the farmers group had eight alternative strategic that can be chosen by the farmers group. Based on the results of the QSPM matrix analysis, from seven alternative strategies there is an alternative strategy that is prioritized by the farmers group, spread the information about Guseta is the healthy lifestyle with TAS score of 5.95.